2015
DOI: 10.1182/blood-2015-02-628461
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function tests, independent of platelet count, are associated with bleeding severity in ITP

Abstract: Key Points• ITP patients differ in their tendency to bleed despite similarly low platelet counts, thereby confounding treatment decisions.• Platelet function tests, independent of platelet count, are associated with bleeding severity in ITP patients.Immune thrombocytopenia (ITP) patients with similarly low platelet counts differ in their tendency to bleed. To determine if differences in platelet function in ITP patients account for this variation in bleeding tendency, we conducted a single-center, cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
127
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 28 publications
7
127
1
Order By: Relevance
“…2 Recently, pediatric ITP patients with lower agonist inducible platelet activity were shown to have more severe bleeding than pediatric ITP patients with higher platelet activity and this association persisted after correction for platelet counts. 3 It is, however, unclear whether this observation also holds for adult ITP patients and how platelet activity in ITP patients compares to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recently, pediatric ITP patients with lower agonist inducible platelet activity were shown to have more severe bleeding than pediatric ITP patients with higher platelet activity and this association persisted after correction for platelet counts. 3 It is, however, unclear whether this observation also holds for adult ITP patients and how platelet activity in ITP patients compares to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of P-selectin exposure and GPIIbIIIa activation by flow cytometry is an accepted approach for quantifying platelet activation, and this approach has been used to characterize platelet activation in patients with thrombocytopenia [8, 17]. Interpretation of the results of such studies is, however, hampered by failure to include controls with similarly low numbers of normally functioning platelets.…”
Section: Resultsmentioning
confidence: 99%
“…Platelet dysfunction likely contributes to bleeding in thrombocytopenic patients [7, 8]. Assessment of platelet function in patients with thrombocytopenia may help to identify patients who are at risk for bleeding and therefore requires a prophylactic platelet transfusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombocytopenia, particularly at markedly low levels, may raise concerns of increased bleeding risk. However, it is increasingly observed that platelet count in isolation is an imprecise predictor of bleeding as patients with similarly low platelet count can demonstrate differing tendencies in bleeding . The recent platelet dose (PLADO) trial found that bleeding occurred over a wide range of platelet counts and that prophylactic platelet transfusion did not prevent bleeding.…”
Section: Introductionmentioning
confidence: 99%